1993
DOI: 10.1159/000187533
|View full text |Cite
|
Sign up to set email alerts
|

Serum Beta-2-Microglobulin Level and Residual Renal Function in Peritoneal Dialysis

Abstract: In 32 noncirrhotic patients on peritoneal dialysis, mean serum β2-microglobulin (sβ2M) was 26.58 ± 12.32 mg/l (9.7-63.5). We found a significant correlation between sβ2M and serum creatinine (sCr; r = 0.760), blood urea nitrogen (BUN; r = 0.573), total creatinine and BUN clearance (r = 0.623 and 0.599, respectively), 24-hour Kt/V (r = 0.638), glomerular filtration rate (r = 0.623), 24-hour urine output (r = 0.669), serum total protein (r = 0.584) (p < 0.01 for all the above r v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 3 publications
1
31
1
Order By: Relevance
“…Apart from removal of small molecular toxins, RRF contributes significantly to the clearance of middle and large molecular weight substances in PD patients 18 . Indeed, patients on PD with RRF have lower levels of β2‐microglobulin than those without RRF 19 …”
Section: Discussionmentioning
confidence: 99%
“…Apart from removal of small molecular toxins, RRF contributes significantly to the clearance of middle and large molecular weight substances in PD patients 18 . Indeed, patients on PD with RRF have lower levels of β2‐microglobulin than those without RRF 19 …”
Section: Discussionmentioning
confidence: 99%
“…RRF is associated with lower levels of middle molecules in PD (63–67) and HD (65,68). Clear evidence already exists that β 2 ‐microglobulin is a major constituent in dialysis‐related amyloid fibrils (69,70), and it has been suggested that RRF may protect against amyloid deposition (71).…”
Section: Potential Explanations For the Survival Benefit Associated Wmentioning
confidence: 99%
“…β2‐microglobulin, advanced glycation end products (AGE), and advanced oxidised protein products (AOPP). RRF is also associated with better phosphate and potassium control, better anaemia correction and reduced erythropoietin stimulating agent consumption, improved nutritional status and quality‐of‐life, enhanced metabolic profiles (reduced internal milieu fluctuations) and improved dialysis patient outcomes 17–24 …”
Section: Is Preservation Of Residual Renal Function a Primary Objectimentioning
confidence: 99%